Pemanfaatan Twitter sebagai Media Pengungkapan Diri Remaja Sidoarjo - Muchammad Royyanul Wahabi; Poppy Febriana (Mahesa Research Center, 2022)
This study aims to find out how the form of twitter as a new medium in self-disclosure carried out by teenagers in Sidoarjo. This study used qualitative research methods. For data collection techniques, interviews, observations, and documentation were carried out to adolescents in Sidoarjo aged between 18-22 years. The theory used in this research is the self-disclosure theory from Johari Window. Social media itself is a medium that is very open to many people. In addition, social media is considered as an online story book among teenagers in Sidoarjo. when we feel a sense of comfort and have trusted others, that is what causes self-disclosure to occur. Self-disclosure can also be done through social media. they can do this consciously or not if their activities are too open and can be used as public consumption for social media users, especially on Twitter social media. Another purpose of this research is to find out the extent to which Sidoarjo teenagers are open in self-disclosure through Twitter social media tweets. The results of this study use Twitter as a medium for self-disclosure of Sidoarjo teenagers in the form of their hearts, feelings, emotions, and thoughts at that time. it was done to lighten the burden on theirself.